Molecular Signatures of Three Fulvic Acid Standard Samples as Revealed by Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry. Issue 47 (19th December 2019) - Qin, Shuai; Xu, Chengbin; Guo, Fei; Qi, Ji; Xu, Lei; Xu, Yingzi; Song, Fanhao; Bai, Yingchen
Abstract: It is necessary to understand the molecular composition of fulvic acid (FA), which plays a significant role in the transport and bioavailability of pollutants in the environment. FA collected from Suwannee River in South Georgia (SRFAriver ) and Elliott soil in fertile prairie of Illinois (ESFAsoil) are two standard fulvic acid samples of International Humic Substances Society (IHSS). FA collected from Beijing Jiufeng forest soils in China (JFFAsoil ) was extracted according to the standard method recommended by IHSS. In this study, the compositions of three FA from two origins (i. e. river and soil) are characterized using negative ion mode electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT‐ICR MS). Compounds possessing higher aromaticity usually contain more nitrogen or sulfur atoms. The aromaticity and humification degree of soil‐derived FA are higher. Soil‐derived FA contains more nitrogen and sulfur elements because compounds containing nitrogen and sulfur atoms are easily absorbed by clay minerals and preserved in aromatic molecules. Comparing the two soil‐derived FA, they differed little in formula and component compositions, but JFFAsoil was slightly more aromatic and less labile than ESFAsoil . These are useful for understanding the difference between the carbon, nitrogen and sulfur element enrichment process in the formation of fulvic acid in river and soil environment at the molecular level. Abstract : Fulvic acid (FA) collected from Suwannee River in South Georgia (SRFAriver ) and Elliott soil in fertile prairie of Illinois (ESFAsoil) are two standard fulvic acid samples of International Humic Substances Society (IHSS). Fulvic acid collected from Beijing Jiufeng forest soils in China (JFFAsoil ) was extracted according to the standard method recommended by IHSS. The aromaticity and humification degree of soil‐derived FA is higher. Meanwhile, nitrogen and sulfur elements mainly exist in aromatic molecules. Hence, the content of Cc Hh Oo Nn Ss formulas in soil‐derived fulvic acid is significantly higher than that in river‐derived fulvic acid, that is, soil‐derived FA contains more heteroatoms (especially nitrogen and sulfur atoms).